Phosphoric acid : purification, uses, technology, and economics - Gilmour, Rodney (Taylor & Francis, 2014)
Preface: "Within three months of joining Albright & Wilson (A&W) and talk of handover plans for the leadership of the corporate engineering department, I was asked to help with its dismantlement, along with corporate research, in a bid to cut company overheads. This was the beginning of a turbulent period, initially of cost saving within A&W and subsequently of rationalization of the combined assets of A&W and Rhodia. Although formal technical reports were secure in company libraries, much of the detailed know-how was lost as experienced employees left. Subsequently, business units were sold off and sometimes closed, with the further loss of corporate memory. Eventually, even central libraries become neglected or even disappear, and knowledge and understanding is lost. Other industrial phosphate companies were going through the same process in a giant chess game of global rationalization. Meanwhile, the pioneers of the technology, whose names appear on the patents, are now old or have passed away. Therefore, I have written this book partly as a review of the technology and its progress since the 1960s to signpost where it came from and where it has got to before all understanding was lost; I have felt at times like the last Mohican. Chapter 1 includes a brief historical review to place the current technology in context. As I began to write it, I suspected that a number of significant technological leaps would emerge, and this has proven to be the case. "-- Provided by publisher.
Keywords: Phosphoric acid.; Phosphoric acid -- Industrial applications.; elektronické knihy; electronic books